Assessing long-term, vestibulotoxic side effects after gentamicin therapy in neonatal sepsis or infection using video head impulse test - Zaubitzer, Lena; Kotzur, Anja; Hegemann, Stefan; Rotter, Nicole; Schell, Angela (Frontiers in Pediatrics, 2024)
Question: Does gentamicin therapy in children with neonatal sepsis or infection lead to persistent vestibulotoxicity? Findings: In a single-center, prospective cross-sectional study video head impulse test (VHIT) was performed to evaluate vestibular function in 23 children aged 3-7 years at least three years after intravenous gentamicin therapy for neonatal sepsis or infection.Although eleven children showed abnormal results in vestibular testing, they did not present with a clinically significant vestibular hypofunction or delayed motoric development.VHIT can serve as a sensitive investigation method for the screening of posttherapeutic vestibulotoxic side effects after gentamicin therapy in children.